g(x)=3x(x-2)

Simple and best practice solution for g(x)=3x(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for g(x)=3x(x-2) equation:


Simplifying
g(x) = 3x(x + -2)

Multiply g * x
gx = 3x(x + -2)

Reorder the terms:
gx = 3x(-2 + x)
gx = (-2 * 3x + x * 3x)
gx = (-6x + 3x2)

Solving
gx = -6x + 3x2

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Divide each side by 'x'.
g = -6 + 3x

Simplifying
g = -6 + 3x

See similar equations:

| -45=3(-3-4m) | | 3x-5+12-4x+14=86 | | 2x+3(6x-4)=128 | | x^2-0.1x-0.6=0 | | 3x^2+75+147=0 | | 90+n+(n-2)=180 | | 7x+3(3x-15)=83 | | x^2-0.1x-0.6x=0 | | 5x+6(4x-17)=130 | | 1.3m-2.1m=-8 | | 5x+(4x-17)=130 | | 15y*14=2(5y+6) | | X-0.3x=13 | | 7x+2(3x-6)=53 | | 10x^2-x-6=0 | | 7x+6(x+8)=139 | | -52=4(3x-4) | | 0.25p-1.75=0.16p-0.5 | | 2lx-1l=6 | | 40+.25m=25+.40m | | 2x+4(x+16)=136 | | 0.5x-0.5(2x+3)=-0.6(x+3) | | x+6=10x^2 | | x+19=x+58 | | sqrtx+6=10x | | 7=(9g-2) | | 2x+6(5x-2)=180 | | 7-3x=4x+3 | | 7x+3(3x-5)=81 | | Xz+9=10z | | -72x^3-8x^2=0 | | 9k+4=27k |

Equations solver categories